The Importance of Vitamin D in the Development of Rickets in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Based on questionnaires and level of 25(OH)D in 466 children under 1 year factors for rickets was identified. Reliable factors were iron deficiency anemia during pregnancy, toxemia of pregnancy of the mother and the lack of vitamin D during first year of life of a child, lack of outdoor stay (less then 20 minutes per day), frequent colds, not effective traditional prevention of rickets vitamin D.